The Moral Philosophy of Four Elements of Modern Urdu Ghazal - Zartashia Sagheer; Tariq Mahmood Hashmi (بازیافت, 2020)
Ghazal is a cultural genre of Persian and Urdu poetry. Duringbritish colonial period in sub-continent ghazal poets was not appreciated  by contemporary criticism but poets much struggled for its thematic and  stylistic development. It is notable that ethics and social moral values are dominating theme in their poetry because of their affiliation with  mysticism. These poets urged on the spiritual values educated by religion  and were established in eastern society.